1997
DOI: 10.1210/endo.138.12.5594
|View full text |Cite
|
Sign up to set email alerts
|

The Vitamin D Analog, KH1060, Is Rapidly Degraded Both in Vivo and in Vitro via Several Pathways: Principal Metabolites Generated Retain Significant Biological Activity*

Abstract: Vitamin D analogs are valuable drugs with established and potential uses in hyperproliferative disorders. Lexacalcitol (KH1060) is over 100 times more active than 1alpha,25-dihydroxyvitamin D3 [1alpha,25-(OH)2D3], as judged by in vitro antiproliferative and cell differentiating assays. The underlying biochemical reasons for the increased biological activity of KH1060 are unknown, but are thought to include 1) metabolic considerations in addition to explanations based upon 2) enhanced stability of KH1060-ligand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…Limited digest proteolysis shows that the 20-epi analog-receptor complexes are more resistant to digestion and suggests that they are more stable. Additionally, an important role might be played by the rate of assimilation and how the synthetic agonists are metabolized vs. the natural ligand in different cell types (25,31). Altogether, these data suggest that the life time of the active conformation is then the main factor responsible for the formation of a more potent complex with coactivators like DRIP and the subsequent higher transcription activity.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Limited digest proteolysis shows that the 20-epi analog-receptor complexes are more resistant to digestion and suggests that they are more stable. Additionally, an important role might be played by the rate of assimilation and how the synthetic agonists are metabolized vs. the natural ligand in different cell types (25,31). Altogether, these data suggest that the life time of the active conformation is then the main factor responsible for the formation of a more potent complex with coactivators like DRIP and the subsequent higher transcription activity.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, the naturally occurring hydroxylation of C24␣ in KH1060 and C23 in 1␣,25(OH) 2 D 3 would form steric clashes with His-305, affecting the hydrogen bond network with 25-OH. The resulting conformational changes can thus explain the reported lack of transcriptional activity (25). Based on the crystal structures, this activity would depend on the capacity of the pocket to accommodate these additional groups.…”
Section: Conformation Of the Bound Ligandsmentioning
confidence: 99%
“…In addition, we have demonstrated that for the 1,25-(OH) 2 D 3 analog KH1060 a cellular/ nuclear context (i.e. the absence or presence of nuclear cofactors) is crucial for observing the ligand-induced VDR-VDRE binding that reflects its increased biological potency (15)(16)(17)(18). Thereby, this study implicates the significance of these nuclear cofactors for determining the extent of transcriptional activity.…”
Section: Discussionmentioning
confidence: 58%
“…In addition, the present paper shows that the increased biological potency of the vitamin D analog KH1060 (15)(16)(17)(18) is not reflected by an increased binding of in vitro synthesized VDR and RXR␣ to various VDREs. KH1060-induced binding of in vitro synthesized VDR/RXR␣ to the mouse osteopontin VDRE was slightly increased, whereas binding to human osteocalcin and rat osteocalcin VDREs was comparable with or even less than 1,25-(OH) 2 RO 24-2637 and RO 23-7553 also demonstrated a lack of parallelism between the potency of these analogs to induce the binding of recombinant human VDR and RXR␣ to the human osteocalcin VDRE and the ability of these analogs to activate a human osteocalcin VDRE-driven reporter gene.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation